Integrasi Ketahanan Karyawan, Pemberdayaan Psikologis, dan Keterlibatan Karyawan : Studi pada Kanvaz Village Resort Seminyak - Ni Nyoman Tri Purnama Dewi; I Gede Riana (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study aims to analyze the integration between psychological empowerment, employee resilience, and employee engagement among employees at Kanvaz Village Resort Seminyak. The study is based on the Job Demands-Resources (JD-R) Theory, which explains that the balance between job demands and job resources influences employee engagement. In this framework, psychological empowerment is positioned as a job resource, while employee resilience functions as a personal resource that enables employees to cope effectively with work-related challenges and pressure. A quantitative research approach was employed using a saturated sampling technique involving all 137 employees of Kanvaz Village Resort Seminyak as research respondents. Data were collected through structured questionnaires and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS software. The findings reveal that psychological empowerment has a positive and significant effect on both employee engagement and employee resilience. Furthermore, employee resilience positively and significantly influences employee engagement and acts as a complementary partial mediator in the relationship between psychological empowerment and employee engagement. These findings highlight the importance of strengthening psychological empowerment and resilience to foster higher levels of employee engagement and support organizational performance in the hospitality industry.